2020
DOI: 10.3390/nu12040897
|View full text |Cite
|
Sign up to set email alerts
|

Schisandra Extract and Ascorbic Acid Synergistically Enhance Cognition in Mice through Modulation of Mitochondrial Respiration

Abstract: Cognitive decline is observed in aging and neurodegenerative diseases, including Alzheimer’s disease (AD) and dementia. Intracellular energy produced via mitochondrial respiration is used in the regulation of synaptic plasticity and structure, including dendritic spine length and density, as well as for the release of neurotrophic factors involved in learning and memory. To date, a few synthetic agents for improving mitochondrial function have been developed for overcoming cognitive impairment. However, no nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Numerous studies have reported that many natural compounds can induce neuronal differentiation, outgrowth, survival, and improved synaptic function in the central nervous system. Jang et al have demonstrated that a mixture of Schisandra chinensis extract (SCE) and ascorbic acid (AA) improved cognitive function and induced synaptic plasticity-regulating proteins by enhancing mitochondrial respiration [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported that many natural compounds can induce neuronal differentiation, outgrowth, survival, and improved synaptic function in the central nervous system. Jang et al have demonstrated that a mixture of Schisandra chinensis extract (SCE) and ascorbic acid (AA) improved cognitive function and induced synaptic plasticity-regulating proteins by enhancing mitochondrial respiration [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Jang et al . found that a mixture of Schisandra Chinensis extract and ascorbic acid improves mitochondrial function and memory and can also be used to alleviate AD and aging-related memory decline (Jang et al, 2020 ). Dextromethorphan (DB00514) is an NMDA receptor antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…The S.chisandra lignan gomisin J up-regulated apoptosis signaling and decreased the dissociation of hexokinase II from the voltage-dependent anion channel (VDAC) in mitochondria, thus reducing aerobic glycolysis in glioma cell lines [ 71 ]. Mixture of S. chinensis extract and ascorbic acid restored mitochondrial respiration, improved cognitive function, and induced synaptic plasticity in mice [ 72 ].…”
Section: Effects Of Schisandra Chinensis Fruit Extract and Its Constituents On Mitochondriamentioning
confidence: 99%